Efektivitas Program Pendidikan Profesi Guru (PPG) terhadap Profesionalisme Guru di UPT SMP Negeri 6 Medan - Islamiyah, Syuwaibatul (Jurnal Manajemen Pendidikan Islam (MANAPI), 2025)
The Teacher Professional Education Program (PPG) is an educational program designed to prepare graduates of undergraduate education and non-education programs to fully master teacher competencies in accordance with national education standards. Teachers as professional educators are evidenced by the possession of an educator certificate obtained through the PPG program. Through PPG, teachers are expected to enhance their ability to master teaching materials, plan, develop, and implement effective and productive learning processes. This study aims to determine the effectiveness of the PPG program in improving teacher professionalism at UPT SMP Negeri 6 Medan. This research employs a qualitative approach with a field research design. Data collection techniques include observation, interviews, and documentation, while data validity is ensured through triangulation. Data analysis is conducted through data reduction, data display, and conclusion drawing. The results of the study indicate that the implementation of the PPG program is effective in improving teachers’ knowledge, skills, attitudes, and motivation, which positively impacts teacher professionalism at UPT SMP Negeri 6 Medan.